2021
DOI: 10.1186/s40100-021-00181-9
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and productivity of farms: a periurban case study analysis

Abstract: Periurban farming systems are characterized by the need to adapt the farming practices coping with a modified natural and social environment. Questions are thus posed on the efficient use of the inputs. The purpose of this study is to estimate the technical efficiency and the productivity of periurban farms. To do so, the study employs a data envelopment analysis that properly captures the heterogeneity of the periurban farming system. The sample considered livestock and crop farms, located in the South Milan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Table 2 showed that most (78.8%) of the youth were unemployed in the study areas. Similarly, [37] [38] reported high unemployed among youth in rural areas. High youth unemployment might lack job opportunities or skills and experience required in our study sites.…”
Section: Employment Status Farming Experience and Landholdingmentioning
confidence: 94%
“…Table 2 showed that most (78.8%) of the youth were unemployed in the study areas. Similarly, [37] [38] reported high unemployed among youth in rural areas. High youth unemployment might lack job opportunities or skills and experience required in our study sites.…”
Section: Employment Status Farming Experience and Landholdingmentioning
confidence: 94%
“…They recommended relevant extension programs to fill in the efficiency gap. Gaviglio et al (2021) carried out a study on crops and livestock farms among 50 randomly sampled farmers in Milan, Italy to determine the level of technical efficiency and the farm productivity. In their study, two models were considered; constant and variable returns to scale DEA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis of economic and financial efficiency of agriculture has long been the subject of numerous studies. Efficiency was studied at the level of the whole agricultural sector [19,20], as well as at the level of plant and animal production holdings [2,6,[21][22][23][24]. In the above-mentioned studies, technical and scale efficiency or inefficiency of the researched objects were determined, the sizes of production gaps were determined and rankings of the researched objects were made according to the efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agriculture is one of the most important sectors of the economy, as it plays a key role in food production and the conservation of natural resources. The economic and financial efficiency of farms, or agricultural sectors [1][2][3][4][5][6][7], has been a central focus of research to date. The World Bank [8] estimates indicate that cereal and meat production will increase by 50% and 85%, respectively, in response to increasing demand between 2000 and 2030.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation